Abdominal Circumference as A Predictor of Type II Diabetes Mellitus in Young Women - Astuti, Siti Choirul Dwi; Apryanti, Yohana Putri (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Obesity is becoming one of the main factors in the increase in non-communicable diseases globally. In Indonesia, the prevalence of central obesity at 15 years and over continues to increase. The increase in visceral fat is related to abnormal metabolisms, such as a decrease in glucose tolerance and insulin sensitivity, causing an increase in blood sugar levels, a risk factor for diabetes. To predict the incidence of type 2 diabetes mellitus, the abdominal circumference is a better predictor than BMI against type 2 diabetes mellitus. This study aims to determine the relationship between abdominal circumference to blood sugar levels in young women. This research is an observational analytical study using the cross-section method. Sampling in this study used a consecutive sample, which was taken based on inclusion and exclusion criteria in the population. The overall subjects of the study amounted to 70 respondents. The results showed a meaningful relationship between the abdominal circumference and fasting blood sugar levels (p = 0.000) with a moderate correlation (r = 0.440) and a significant relationship between abdominal circumference to blood sugar levels 2 hours after glucose loading (p = 0.030) with a weak correlation (r = 0.259). This study concluded that there is a relationship between abdominal circumference and blood sugar levels using an oral glucose tolerance test in young women. As a recommendation, young women should maintain their lifestyle and keep their abdominal circumference not exceeding 80 centimeters to prevent diabetes.